Impeller design for centrifugal pump with number of 5 blades driven four stroke 40 cc petrol engine - Gunawan, Iwan; Arifin, Zainal (Program Studi Teknik Mesin Fakultas Teknik Universitas Pasundan, 2025)
An impeller with five blades was designed to enhance water discharge from the volute. The increased number of blades was expected to exert a more potent force on the water due to a larger surface area. However, excessive blade numbers could obstruct inlet water flow, reducing discharge efficiency. Therefore, a restriction was applied to optimize the blade count. The impeller was developed using an experimental approach, as most designs typically feature four to seven blades. Performance tests were conducted by varying the outlet pipe width through different valve openings, and the effects on water discharge and velocity were analyzed. The results indicated that increasing the rotational speed (rpm) led to a higher discharge rate. At 5,702 rpm with a 100% valve opening, the maximum discharge of 1.426 L/s was achieved, while at 3,536 rpm with a 25% valve opening, the lowest discharge of 0.18 L/s was recorded. The velocity analysis showed that the highest speed of 14.17 m/s occurred at 5,702 rpm with a 25% valve opening, whereas the lowest speed of 2.74 m/s was observed at 3,536 rpm with a fully open valve. These findings confirm that increased valve openings enhance discharge and reduce water velocity due to outlet pipe diameter variations. .